KONSEP IMPLEMENTASI ILMU SOSIAL DAN ALAMIAH DASAR DALAM KEHIDUPAN BERMASYARAKAT (STUDI ANALISIS PENERAPAN ILMU PENGETAHUAN DAN TEKNOLOGI) - Ernata Hadi Sujito (Institut Agama Islam Darul Ulum Kandangan, 2018)
Abstrak: Basic Social Sciences and Natural Sciences is one of the most important sciences, which must be possessed by a student, who is prepared to become a Leader either among the Bureaucracy or among the Community. Along with the development of time, we can study the Social Sciences and Basic Natural Sciences by using Science and Technology, so that the integration of Science will be easier in developing the Social Sciences. On this occasion we will discuss a number of things, about the positive and negative impacts of the influence of Social Sciences with the development of current science and technology, including: Impact on Human Needs; Impact on the Utilization of Natural Resources; Impact on Natural Resources; Impact on Human Resources; Impact on Communication and Transportation; Impact on Health Improvement; Impact on Achievement of Prosperity.